2004
DOI: 10.1063/1.1689761
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high magnetic field on phase stability in Fe-Ni

Abstract: Identically prepared samples of Fe0.85Ni0.15 were annealed either in the ambient magnetic field or in a field of 29 T. Room temperature x-ray powder diffraction measurements that were performed after magnetic annealing showed that the ratio of the volume of the γ to α phase is decreased in the field-annealed sample by a factor of 2. First-principles calculations of the magnetic structure in the presence of a magnetic field are used to compute the resulting change in free energy. Analysis in terms of the phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In conclusion, let us note that the authors of [16][17][18][19][20] have already mentioned that the applied magnetic field should be added to the list of the known thermodynamic variables. They also showed examples where the application of an external magnetic field results in the new T-c paths of an alloy evolution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, let us note that the authors of [16][17][18][19][20] have already mentioned that the applied magnetic field should be added to the list of the known thermodynamic variables. They also showed examples where the application of an external magnetic field results in the new T-c paths of an alloy evolution.…”
Section: Resultsmentioning
confidence: 99%
“…The evaluation of thermodynamic changes induced by the applied magnetic-field effects on the local magnetic moments showed [17] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Work in ferrous materials has demonstrated that high magnetic field processing (HMFP) can induce meaningful changes in kinetics, phase equilibria, and solubility limits in the solid state. [1][2][3] These processing routes can result in modified microstructures that, for example, retain alloying elements in solution. This potentially negates the need for a solution heat treatments and/or increase maximum solid solubility limits, improving the strength of the alloy.…”
Section: Introductionmentioning
confidence: 99%
“…It allows the customization of the structure of the material at micro-scale and nano-scale levels in order to tailor the properties and performance of the material. Thermomagnetic processing technology has been successfully used with alloys to selectively control microstructure stability and phase transformation kinetics [91][92][93] . However, the utilization of this technology with polymeric materials has not been fully explored, and therefore the ability to control molecular orientation of the polymer matrix in advanced composites is expected to enable unique mechanical, thermal, and electric properties of structural and functional composites.…”
Section: Introductionmentioning
confidence: 99%